Thermo-Fluid Dynamics of PLA Deposition in Fused Filament Fabrication 3D Printing: A Numerical Study - Zaki Saptari Saldi; Purba Purnama; Nurmalia Nurmalia; Salman Alfarisi; Muhammad Arifin; Ammar Munadi Suweco (Department of Physics, Sebelas Maret University, 2025)
Prototyping plays an important role in product design and has recently gained benefit from the rising popularity of 3D printing. It is to be expected that 3D printing will accommodate more materials, which need to be tailored to specific design requirements. Insights into heat transfer and fluid flows (thermo-fluid dynamics) in the printing process is thus essential to obtain favorable process parameters that can lead to high quality prints. In this work, polylactic acid (PLA) melt in Fused Filament Fabrication (FFF) 3D printing was numerically studied through Computational Fluid Dynamics (CFD) simulations, with a focus on the thermo-fluid dynamics of the strand deposition of the filament melt on the printer platform. The study was carried out by evaluating 6 printing cases, with a variation of 2 key process parameters, i.e., printing speed (30 and 45 mm/s) and platform temperature (310, 320, and 340 K). The simulation results showed that the free surface in the tip region of the strand has the most tendency to adhere to the printing platform heated at 340 K with the printing speed of 45 mm/s, as compared with other cases. This was affected by the lower dynamic viscosity in the region, relative to other cases, resulting from the high platform temperature and shear rate generated by the high printing speed.